Fotografias da Lingüística Aplicada no campo de línguas estrangeiras no Brasil - Lopes, Luiz Paulo da Moita (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2018)
This paper presents photographs of the field of Applied Linguistics (AL) in the area of foreign language (FL) in Brazil in the last thirty years. The photographs focus on: the increase in the number of AL programmes, most favored dissertation and thesis topics, the foundation of FL teachers’ associations and of the Brazilian Association for Applied Linguistics, the Brazilian English for Specific Purpose Project, the main periodicals and books published in the field, and the Brazilian National Parameters for FL Education. By way of conclusion, the paper presents virtual photographs of the area as a way of pointing to what is to come in the future: a multilingual foreign language education policy, the foundation of new AL programmes, research areas to be developed and theoretical and methodological approaches to be favored.